Synthesis, Spectral Studies and Antifungal Activity of β-Diketonate Complexes of Bimetallic Organotin(IV) aluminium(III)-μ-oxoalkoxides - KUMAR, SUNIL; Sonika (Asian Journal of Chemistry, 2010)
Organotin derivatives of the type PhMeSn(OAc)OAl (OPri)(L), PhMeSn(OAc)OAl(L)2, PhMeSnO2Al2(OPri)3(L) and PhMeSnO2Al2(OPri)2(L)2 have been synthesized by the reaction of PhMeSn(OAc)OAl(OPri)2 (1) and PhMeSnO2Al2 (OPri)4 (2) with β-diketones in 1:1 and 1:2 molar ratio in refluxing benzene. These complexes have been characterized by elemental analysis and spectral studies (IR, 1H, 13C, 27Al and 119Sn NMR). The results of antifungal activity of the complexes as well as precursors have also been recorded and discussed with the standard fungicide against Colletotrichum falcatum.